Trends in deaths and disability-adjusted life-years of stroke attributable to high body-mass index worldwide, 1990–2019 - Guo, Xiucai; Li, Junxiao; Yin, Xueyan; Zhang, Ziping; Zhong, Qiongqiong; Zhu, Feng (Frontiers in Neurology, 2023)
Background High body mass index (HBMI) is an independent risk factor for stroke. Previous studies on the incremental burden of the rapid growth of stroke attributable to HBMI are incomplete and lag behind. We aim to assess the global burden of stroke attributable to HBMI based on a public database online. Materials and methods Study data were taken from the Global Burden of Disease, Injuries, and Risk Factors Study; deaths, the Disability-Adjusted Life-Years (DALYs), and their age-standardized rates were screened. The join point regression was used, wherein age-standardized rates were referred to as temporal trends in disease burden. Results Deaths from stroke attributable to HBMI worldwide were on the rise during 1990–2019, with an increase of 88.75%. Age-standardized DALYs were on the rise during 1990–2003 but declined during 2003–2013, with a turning point in 2013 and an increasing trend since then [the Annual Percentage Change (APC) = 0.30%, p < 0.05]. China, India, Indonesia, the Russian Federation, and the United States of America shared in sequence the rate of leading deaths and DALYs in 2019. The Socio-Demographic Index (SDI) was associated with an increasing trend in age-standardized deaths (R = −0.24, p < 0.001) and age-standardized DALYs (R = −0.22, p = 0.0018). Conclusion A range of indicators for the global burden of stroke attributable to HBMI have been on the rise for the past three decades. Tremendous efforts worldwide should be in place to control and treat stroke attributable to HBMI, especially in regions with high-middle and middle SDIs and among middle-aged and aged populations.